Carbonic Anhydrase XII as an Independent Prognostic Factor in Advanced Esophageal Squamous Cell Carcinoma - Ochi, Fumiaki (J Cancer, 2015)
Background: Although recent studies described important roles for carbonic anhydrase (CA) XII in epithelial carcinogenesis and tumor behavior, a consensus has not yet been reached regarding its clinicopathological significance in esophageal squamous cell carcinoma (ESCC). In the present study, we investigated its prognostic significance in ESCC. Materials and Methods: An immunohistochemical analysis was performed on 70 primary tumor samples obtained from ESCC patients who underwent esophagectomy, and the relationships between the expression of CA XII and various clinicopathological features or prognosis were analyzed. Results: Immunohistochemical staining showed that CA XII was primarily found in the cell membranes of carcinoma cells. Although the expression of CA XII was related to the pT category, it had no prognostic impact. We then examined the expression of CA XII according to the pT category. In pT2-3 ESCC, the 3-year survival rate of patients with the high grade expression of CA XII (29.1 %) was significantly lower than that of patients with the low grade expression of CA XII (70.3 %). Furthermore, a multivariate analysis demonstrated that the expression of CA XII was one of the most important independent prognostic factors following radical esophagectomy in pT2-3 ESCC. Conclusion: These results suggest that the expression of CA XII may be a valuable prognostic factor for patients with advanced ESCC. The results of the present study provide an insight into the role of CA XII as a biomarker in ESCC.